Петр Чайковский. Родина гения: [фотоальбом / составитель: Г. Г. Грязев] - Грязев Георгий Геннадьевич (Удмуртия, 2016)
Экземпляры: ф.18 (20200922) / Инвентарный номер: 3542 / Цена: / Сис.шифр: 85.313(2Рос.Удм)1-8 / Авт.знак: Ч-15 / ГРНТИ: 18.41.91 / ББК: 85.313(2)1-8